Analisis Kepemimpinan Transformasional di Sekolah Menengah Kejuruan terhadap Kinerja Guru: Sebuah Studi Tinjauan Pustaka - Deni Sartika; M. Giatman; Jonni Mardizal; Yuliarma Yuliarma (Journal of Education and Teaching Learning, 2026)
Vocational High Schools play a strategic role in preparing competent human resources aligned with industry demands. The quality of vocational education is closely related to teacher performance, which is influenced by leadership practices implemented by school principals. Transformational leadership is considered a relevant leadership approach in educational management because it emphasizes inspirational vision, intellectual stimulation, individualized consideration, and motivational influence. However, previous empirical findings regarding the relationship between transformational leadership and teacher performance show varying results, creating the need for a comprehensive synthesis. This study aims to analyze the effect of transformational leadership on teacher performance in Vocational High Schools through a literature review approach. Relevant scientific articles published between 2017 and 2026 were collected from Google Scholar and ScienceDirect using keywords related to transformational leadership and teacher performance in Vocational High Schools. After screening and applying inclusion criteria, the selected articles were analyzed descriptively and comparatively. The findings indicate that most studies report a positive and significant relationship between transformational leadership and teacher performance, either directly or indirectly through mediating variables such as work motivation, organizational commitment, and job satisfaction. Overall, transformational leadership contributes to improving teacher effectiveness and the quality of vocational education.